Scarless integumentary wound healing in the mammalian fetus: Molecular basis and therapeutic implications - Kathju, Sandeep; Gallo, Phillip H.; Satish, Latha (Birth defects research. Part C. Embryo today, 2012)
Adult mammals respond to injury of their skin/integument by forming scar tissue. Scar is useful in rapidly sealing an injured area, but can also lead to significant morbidity. Mammals in fetal life retain the ability to heal integumentary wounds regeneratively, without scar. The critical molecular mechanisms governing this remarkable phenomenon have been a subject of great interest, in the hopes that these could be dissected and recapitulated in the healing adult wound, with the goal of inducing scarless healing in injured patients. Multiple lines of investigation spanning decades have implicated a number of factors in distinguishing scarless from fibrotic wound healing, including most prominently transforming growth factor‐β and interleukin‐10, among others. Therapeutic interventions to try to mitigate scarring in adult wounds have been developed out of these studies, and have reached the level of clinical trials in humans, although as yet no FDA‐approved treatment exists. More recent expressomic studies have revealed many more genes that are differentially expressed in scarlessly healing fetal wounds compared with adult, and microRNAs have also been identified as participating in the fetal wound healing response. These represent an even greater range of potential therapeutics (or targets for therapy) to translate the promise of scarless fetal wound healing to the injured adult patient. Birth Defects Research (Part C) 96:223–236, 2012. © 2012 Wiley Periodicals, Inc.